Accuracy of frozen section diagnosis in ovarian tumors: Is there a change in the course of time?. Issue 5 (1st August 2003) - Gol, M.; Baloglu, A.; Yigit, S.; Dogan, M.; Aydin, Ç.; Yensel, U.
Abstract : A retrospective study of 222 ovarian biopsy results between January 1, 2000 and August 31, 2002 was examined to determine the accuracy of frozen section diagnosis. In addition we reviewed all previous studies that examined the accuracy rates of frozen section diagnosis in ovarian tumors. Histopathologic examination results of frozen section biopsies were concordant with paraffin diagnosis in 92% of all cases. The sensitivity rates for benign, malignant, and borderline ovarian tumors were 98%, 88.7%, and 61%, respectively. There were five (2.2%) false-positive (overdiagnosed), and 13 (5.4%) false-negative (underdiagnosed) patients in frozen section examination. Frozen section examination of mucinous tumors showed higher underdiagnosis rates (20%). Review of previous studies showed no significant variation in accuracy rates of frozen section diagnosis for benign and malignant ovarian tumors, in relation with time. We found low accuracy rates for borderline ovarian tumors which was similar with the previous studies. Hovewer, there were consistent and relatively higher sensitivity rates for borderline ovarian tumors in the recent studies. As a result, we conclude that frozen section evaluation in identifying a malignant or benign ovarian tumor is accurate enough for the correct diagnosis. Since accuracy rates for borderline ovarian tumors are low, we should have more improvement in the correct diagnosis.